ANALISIS KANDUNGAN UNSUR FOSFOR (P) DALAM KOMPOS ORGANIK LIMBAH JAMUR DENGAN AKTIVATOR AMPAS TAHU - Aziz, Abdul (Bioscientist : Jurnal Ilmiah Biologi, 2013)
Phosphorus (P) is a fluorescent substance due to phosphorescence, a chemical element that has the symbol P with atomic number 15. Phosphorus is an essential macro nutrient essential for plant growth, but its content in soil is lower than nitrogen (N ), potassium (K), and calcium (Ca). The purpose of this research is to know how to analyze the content of phosphorus (P) element in organic compost of mushroom waste with dregs activator know. The method used in this research is quantitative and qualitative. This type of research is experimental research, which is a systematic, logical, and meticulous type of research in controlling the existing conditions. Analysis of data used, namely SPSS 16.0 for Windows followed by Duncan test. The results of this study indicate that compost control with compost treatment has not much different results, respectively, ie (0.84%, 1.00%, and 1.08%) and the highest is the bottom sample. While the composition of the treatment of 10:50 has a sequential result, ie (1.15%, 0.70%, and 0.98%) the highest yield is in the upper sample, the compost treatment of 30:50 has the following results, ie (0.79%, 1.06%, and 1.13 The highest yield was found in the bottom sample, and the 50: 50 treatment compost had a sequential result, ie (0.68%, 0.71%, and 0.69%) the highest yield was in the middle sample.It was concluded that there was no effect of tofu waste in composting organic mushroom waste in lieu of EM4, except with the treatment of 10:50 and 30:50.